2021
DOI: 10.1002/rcs.2256
|View full text |Cite
|
Sign up to set email alerts
|

Navigation assisted total knee arthroplasty in 54,114 patients: No increased risk in acute complications and hospital utilisation

Abstract: Background The advent of navigation in total knee arthroplasty (TKA) has generated interest in attempt to improve component positioning as desired and clinical outcomes. The aim of this study was to evaluate 90‐day complication and cost of navigation‐assisted TKAs (NTKA) compared to conventional TKAs (CTKA) using a national database. Methods A retrospective review of national database was conducted on all patients who underwent TKA from 2010 and 2017. The cohort was stratified into NTKA and CTKA subcohorts, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Patients undergoing TA-TKA had lower complication rates than those undergoing U-TKA. A recent meta-analysis comparing robotic and unassisted TKA observed similar complication rates between groups [ 30 ], though some analyses comparing computer-assisted and unassisted TKA have demonstrated lower complication rates in those undergoing computer-assisted TKA [ 8 , 13 ]. In our study, TA-TKA patients had significantly lower postoperative transfusion rates compared with U-TKA patients, which is consistent with prior findings [ 8 , 13 , 28 ] and associated with improved surgical outcomes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients undergoing TA-TKA had lower complication rates than those undergoing U-TKA. A recent meta-analysis comparing robotic and unassisted TKA observed similar complication rates between groups [ 30 ], though some analyses comparing computer-assisted and unassisted TKA have demonstrated lower complication rates in those undergoing computer-assisted TKA [ 8 , 13 ]. In our study, TA-TKA patients had significantly lower postoperative transfusion rates compared with U-TKA patients, which is consistent with prior findings [ 8 , 13 , 28 ] and associated with improved surgical outcomes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative readmission rates did not significantly differ between groups. In prior national database analyses, computer-assisted TKA has yielded similar [ 25 ] and decreased [ 13 ] readmission rates. Further analysis revealed that patients in the TA-TKA cohort were readmitted primarily for superficial surgical site infections and hematological issues in addition to unspecified and other medical diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the need to enhance the accuracy of surgery, computer‐assisted surgery (CAS) has been continuously advancing in the domain of total knee arthroplasty (TKA) surgery 1–3 . CAS started a few decades ago as computed tomography (CT)‐based/imageless navigation surgery, and the technology developed into robotically assisted surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital and surgeon volume is also known to be related to patient outcomes following THA and TKA, but these data are often not available in administrative claims databases and thus cannot be accounted for. Our review of the literature identified studies in which computer-assisted (9 studies) and/or robotic-assisted technology (11 studies) was evaluated with use of large databases, and none reported surgeon or hospital-specific volume (Table I) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] .…”
mentioning
confidence: 99%